Barriers and Facilitators of Community-Based Health Insurance Policy Renewal in Low- and Middle-Income Countries: A Systematic Review - Hussien M; Azage M (Dove Medical Press, 2021)
Mohammed Hussien,1 Muluken Azage2 1Department of Health Systems Management and Health Economics, School of Public Health, College of Medicine and Health Sciences, Bahir Dar University, Bahir Dar, Ethiopia; 2Department of Environmental Health, School of Public Health, College of Medicine and Health Sciences, Bahir Dar University, Bahir Dar, EthiopiaCorrespondence: Mohammed HussienDepartment of Health Systems Management and Health Economics, School of Public Health, College of Medicine and Health Sciences, Bahir Dar University, P.O. Box: 79, Bahir Dar, 6000, EthiopiaTel +251 588209834Email muhamedun@gmail.comPurpose: A growing number of low- and middle-income countries are implementing small-scale community-based health insurance schemes to tackle the burdens posed by direct out-of-pocket payments. Apart from a few successful experiences, such schemes suffer from the problem of persistent low membership which could be attributed to either initial low enrollment or low renewal rate. However, there is a lack of comprehensive information on the factors that influence subscribers’ policy renewal decisions. Hence, we systematically synthesize information to answer the review question ”what are the barriers and facilitators of community-based health insurance policy renewal in low and middle-income countries?”.Methods: We searched PubMed, Scopus, and Hinari electronic databases in line with the PRISMA guidelines. Our search was limited to studies published from January 2005 to February 2020 in the English language. Additional studies and grey literature were searched using Google Scholar. We included quantitative, qualitative, and mixed-method studies in the review. We assessed the methodological quality of the studies using standardized appraisal tools. The findings were synthesized inductively using a thematic analysis approach.Results: Our searches retrieved 2386 records among which 27 were included in the review. The thematic synthesis identified six major themes that influence the decision to renew scheme policy: socio-demographic factors; scheme-related awareness and understanding; participation in scheme and other voluntary groupings, need and benefit factors; health-care quality; and scheme operation and policy.Conclusion: Lower socioeconomic status, poor quality of health care, lack of benefit from the scheme, lack of trust in scheme management, and dissatisfaction with scheme services are important barriers for community-based health insurance policy renewal. Better education, understanding the principles of the scheme, active participation in the scheme, and long-term illness experience of member households facilitate renewal decisions. These are important areas of intervention for governments and other relevant stakeholders to retain members and maintain the sustainability of the schemes.Registration: The review protocol was registered in PROSPERO international prospective register of systematic reviews (ID = CRD42020168971).Keywords: universal health coverage, community-based health insurance, barriers and facilitators, renewal, low- and middle-income countries